Tribological Behavior of Micro Coir Filler Reinforced Polymer Composite under Dry, Wet, and Heated Contact Condition - Rajdeep Paul; Sumit Bhowmik (Journal of Natural Fibers, 2022)
This article speculated the wear and frictional performance of treated micro coir filler reinforced polymer composite. The surface of the coir filler is modified by the alkali treatment and the composite is prepared with a variation of coir filler reinforcement. The investigation of wear test is steered under dry sliding contact, wet and heated contact state using the pin-on-disk multi-tribometer counter to a stainless steel disc. Experiments 1were conducted considering three different parameters, namely, different normal load (5–40 N), sliding velocity 100 cm/s, and sliding distance (0–2000 m). The results showed that the wear behavior of coir filler-reinforced composite is highly dependent on operating parameters and filler reinforcement. The specific wear rate is lesser in wet contact conditions compared to dry and heated contact conditions. Moreover, lower coir filler loading presented enhanced wear presentation related to the higher filler loading composite. From microscopic images, some micro and macro cracks, debonding, and plastic deformation are witnessed on the worn surfaces of the composite.